Hysteresis Dynamic Behavior of Pneumatic Artificial Muscle - Phuong, Vo Ngoc Yen; Trinh, V.C (The Indonesian Institute of Science and Technology Research, 2024)
The purpose of this work paper is to analyze the effects of friction on the hysteresis dynamic behavior of pneumatic artificial muscle (PAM). Due to the structure of the PAM, the dynamic response is not only affected by the compressed air but also the friction phenomenon. Indeed, the pipe of the PAM called the bellow is made from rubber simultaneously reinforced by metal fibers that are wrapped around the bellow. Hence, the effect of the friction between fibers, between fiber and rubber will be considered in the nonlinear dynamic of the PAM. From dynamic analysis, the complex stiffness model will be attained and analyzed. Comparison between the analysis model and experimental results is realized subjected to harmonic displacement excitation. The results proved the effectiveness of the analysis model. The studied model is a suitable tool in the field of systems vibration analysis using PAM as an elastic element, actuator.